Two Decades in Five Years: Mapping Digital HR, Workflow Automation, and Innovation Ecosystem Research (2020–2025) - Arciana Damayanti; Asep Miftahuddin; Rofi Rofaida; Yoga Perdana; Rizqiana Arifatul Husna; Juliana Juliana (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Digital transformation has reshaped human resource management (HRM), giving rise to digital HR practices, workflow automation and innovation-ecosystem approaches. However, the literature on Digital HRM, electronic HRM (e-HRM), and innovation ecosystems remains scattered across disciplines and themes, leaving the field's intellectual structure, thematic evolution, and future directions only partially understood. This study reviews and maps research on digital human resource management, workflow automation, and innovation ecosystems published between 2020 and 2025 using a systematic literature review (SLR) combined with bibliometric analysis and following the PRISMA 2020 framework for a transparent and reproducible selection process. An initial search of the Scopus database returned 2,163 documents for review. After applying predefined inclusion and exclusion criteria, 244 journal articles were retained and analysed in Bibliometrix and Biblioshiny to examine publication trends, influential authors, journals, countries, and institutions, along with keyword co-occurrence and thematic structures. Research activity rose sharply over the period, at an annual growth rate of 23.84%, with the conceptual core of the field centring on e-HRM, digital HRM, digital transformation, workflow automation and innovation ecosystems. The thematic map identified technology, Industry 4.0, Society 5.0, and helix-based innovation models as the dominant driving themes. The Triple Helix and Quintuple Helix frameworks are well established, whereas Pentahelix-related work remains underexplored and is still emerging. This study offers a comprehensive picture of the intellectual landscape of digital HR transformation and innovation-ecosystem research and points to a clear opportunity for future work: bringing together workflow automation, digital HR practices, and Pentahelix-based collaboration to support sustainable workforce transformation and organizational innovation.